A Voyage To Lilliput of Gulliver's Travel: Environmental Hedonism - Arin Mantara Anggawirya; Lastika Ary Prihandoko (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
This paper analyzes the notion of environment pictured in Gulliver’s Travel: A Voyage to Lilliput by Jonathan Swift in 1762. In analyzing the environment, the writers related some issues in this novel to the concept of eco-cosmopolitan society by P. Marland, and elaborating the issues of environment in this novel through the concept of ecocriticism by L. Buell. Through Gulliver’s travel: a Voyage to Lilliput, the notions of Plague, Economical Crisis, Famine and Environmental hedonism were pictured. Lilliput society that living with Gulliver rise another perspective on seeing the environment, which gives the illustration on how these small creatures adapt to sustain Gulliver as a giant